Quick selection guide to chemical protective clothing - Forsberg, Krister, 1943-; Van den Borre, Ann, 1972-; Henry, N. W.; Zeigler, James Patton, 1952- (Wiley, 2020)
"Chemical Protective Clothing is the last line of defense for protecting the skin, so care must be taken to ensure it provides the protection expected. However, no glove or suit material is resistant to all chemicals. Each barrier material and chemical has it own interaction. Some chemicals will pass through or permeate the barrier in a few seconds, while other chemicals break through the barrier after 8 hours. Information specifying the best protective material is what the user needs quickly. Trade Name Table has been updated with 25 product name changes, 8 new products and 10 products deletions. 12 products in the Master Chemical Resistance Table have changed names and two products have been replaced with 2 important new ones. Many new selection recommendations (color codes) has been added to the table due to new chemicals and additional tests. The chemicals in the index are linked to the UN pictograms related to skin exposure the code letters . This pocket guide is the only independent source for selection of chemical protective clothing. It gives the users the ability to compare the performance of available garment/barrier materials on the market"--